CONTRIBUTION OF HEALTH LITERACY TO INCREASING ANTENATAL CARE COVERAGE IN AN EFFORT TO REDUCE STUNTING - Nurlina, Nurlina (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Background: The results of the 2021 Indonesian Nutritional Status Study report the prevalence of stunting under five in Jeneponto Regency with the highest stunting prevalence of 37.9%, so it is included in the Chronic-Acute category (Stunted ? 20% and Wasted ? 5%). Health literacy plays an important role during pregnancy, influencing the health behavior of the mother and the health of her baby, especially nutrition and child health, such as the problem of stunting in Indonesia.Objective: To determine the contribution of pregnant women's health literacy to increasing the coverage of antenatal services in an effort to reduce stunting.Research method: Using analytical observation with a Cross Sectional Study approach. The sampling method is purposive sampling. The number of samples in this study was 96 respondents. The data collection tool used was the HLS-EU-SQ10-IDN questionnaire. This research was conducted in the Working Area of the Turatea Public Health Center, Jeneponto Regency, from July 2023 to August 2023. Data analysis used SPSS 26 with the Chi Square Test.Results: The results of the chi-square test showed a P-value = 0.039 with ? = 005, so there was a relationship between Education and the Level of Health Literacy for Pregnant Women in the Working Area of the Turatea Health Center, Jeneponto Regency. There is a relationship between ANC Visits and the Health Literacy Level of Pregnant Women in the Working Area of the Turatea Public Health Center, Jeneponto Regency, obtained p = 0.014 with ? = 0.05.Conclusion:Education affects a person's ability to understand, make decisions about their own health and the health of the unborn child. Routine ANC visits provide an opportunity for pregnant women to gain knowledge about the importance of good nutrition during pregnancy, including the importance of adequate nutritional intake. Pregnant women who have a good level of health literacy will be more likely to understand and apply appropriate nutritional recommendations, which can help prevent stunting in the fetus